The best copula modeling of dependence structure among gold, oil prices, and U.S. currency - Pathairat Pastpipatkul (2018)
© Springer International Publishing AG 2016. As internationally traded commodities typically depend on the value of US dollar, this paper especially focuses on the most traded commodities, gold and crude oil, and tries to examine the dependence structures between these variables and the US currency. We employ various types of copulas i.e. the multivariate copula, vine copula, and the Markov switching copula and examine for the best-fit copula functions to model the dependency. Evidence from this study shows that gold and oil prices follow an inverse relationship with the value of US dollar but the relationship between gold and oil itself is strongly positive. However, the pair copulas given condition by another variable results in some attractive correlations.